(3GdJfejI GdEbJUGOjI (B:s (3fXQjGJ hSjGSGJ hehVhYGJ (B/s - (3GdbQjTj, eOMJs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2007)
(3GdJNda GdCbJUGOj eYGjjQg hSeGJg, GdfXQjGJ GdeaSQI ddJNda GdEbJUGOj, fXQjGJ Gdfeh GdEbJUGOj, fXQjGJ GdJfejI GdEbJUGOjI, GdJfejI GdEbJUGOjI GHYGOgG heSJdReGJgG, YbHGJ aj WQjb GdJfejI, GSJQGJjLjGJ GdJfejI GdEbJUGOjI, Jehjd GdJfejI, SjGSGJ GdJfejI GdEbJUGOjI, JhRjY GdehGQO GdEbJUGOjI, ehVhYGJ NGUI aj GdJfejI GdEbJUGOjIs
(3HHdjhZQGajG(B: (3U(B.295s
Keywords: (3GdJNda GdEbJUGOjs; (3GdJfejI GdEbJUGOjIs